Buryak V.G., Buryak V.V, Drapak L.S., Buryak A.V. Analysis of microstructure characteristics of surfaces of composite cutting plates - Буряк, В. Г.; Буряк, В. В.; Драпак, Л. С.; Буряк, А. В. (Problems of Tribology, 2018)
An analysis of the characteristics of the microstructure of the surfaces of composite cutting plates is carried out. The results of investigations of the microstructure change of the working surfaces of sintered and primary and reattached plates are considered. It was established that the working surfaces of plates, sintered and primed ground and re-grounded under the same conditions of technological processes, - their surfaces differ in different density of distribution of super hard grains (light spots), in the number of large and small spots on the surface. An analysis of the standard roughness parameters of the working surfaces of cutting plates from different brands of composite tool materials allows us to conclude that the isotropic kind of rough surfaces after sharpening. Taking into account the roughness parameters, the characteristics of the structural and energy state of the working surfaces of the composite cutting plates can be estimated by the optical system of electronic devices, while using the image diagram of the surfaces with the elements of absorption, The obtained research results are the initial data when using the methodology of performance evaluation of cutting tools by analyzing the acoustic characteristics of the energy state of processing and instrumental materials using the differential equation of cause and effect relationship.